2013
DOI: 10.1016/j.ajem.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-convulsive seizure and other electroencephalographic abnormalities in ED patients with altered mental status

Abstract: Four to ten percent of patients evaluated in emergency departments (ED) present with altered mental status (AMS). The prevalence of non-convulsive seizure (NCS) and other electroencephalographic (EEG) abnormalities in this population is unknown Objectives To identify the prevalence of NCS and other EEG abnormalities in ED patients with AMS. Methods A prospective observational study at two urban ED. Inclusion: patients ≥13 years old with AMS. Exclusion: An easily correctable cause of AMS (e.g. hypoglycemia).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 23 publications
2
35
2
1
Order By: Relevance
“…In previous studies, NCSE was observed in 8% of comatose patients in an ICU [1], in 5% of all patients with altered mental status attending emergency departments [2], in 9.3% inpatients referred for EEG with clinical suspicion of NCSE [3], and in 9.8% of inpatient emergent EEGs [4]. The frequency in our study was lower compared to the above numbers as our denominator was all the inpatient EEGs.…”
Section: Discussioncontrasting
confidence: 64%
“…In previous studies, NCSE was observed in 8% of comatose patients in an ICU [1], in 5% of all patients with altered mental status attending emergency departments [2], in 9.3% inpatients referred for EEG with clinical suspicion of NCSE [3], and in 9.8% of inpatient emergent EEGs [4]. The frequency in our study was lower compared to the above numbers as our denominator was all the inpatient EEGs.…”
Section: Discussioncontrasting
confidence: 64%
“…This contrasts with a study based in a US emergency department that found a prevalence of NCSE of 3% among a selected group of adults (median age 60 years, range 45–76, 259 EEGs performed) presenting with altered mental status (ranging from lethargy to coma) 8. A French study that looked at patients aged >60 (mean age 76, range 60–97, 44 EEGs performed) who had had an EEG to determine the cause of confusion of unknown origin (after initial investigations did not reveal the answer) found that 16% had EEG traces compatible with NCSE 9.…”
Section: Introductioncontrasting
confidence: 78%
“…The 2-hour work-up period cutoff for T1 and T2 was selected based on the median time for enrollment to completion of EEG using microEEG in our previous study. 4 …”
Section: Methodsmentioning
confidence: 99%
“…3 The new microEEG also shortens the duration and amount of preparation needed to obtain an EEG without interfering with other ongoing diagnostic testing. 4 The wireless aspect allows real-time reporting of EEG results, which has the potential to affect clinical care.…”
mentioning
confidence: 99%